PENERAPAN METODE QUANTUM WRITING UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI DI KELAS X TP2 SMK KB PUSDIKPAL - Ani Setiani; Wikanengsih Wikanengsih; Aurelia Sakti Yani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
One of the skills in writing at school is writing poetry in Indonesian subjects. Based on empirical data in the field, researchers often find that when students are given learning to write poetry, many students are less enthusiastic and do not really take part in writing poetry. One alternative solution to problems in overcoming difficulties is to increase creativity, motivation and the ability to write poetry in class X, namely by using the Quantum Writing Method. The Quantum Writing method is a learning method that refers to the quantum learning model. This study used a Classroom Action Research design. The subjects of this research were 20 students of class X TP2 KB Pusdikpal SMK. The instruments used were observation and tests. Data collection techniques in this study include observation, interviews and documentation. Based on the results, it is known that the application of the Quantum Writing learning method in class X TP2 of SMK KB Pusdikpal can improve learning to write poetry. The average score of students in cycle 1 in writing poetry using the Quantum Writer method after receiving 69.5 actions or is in the enough category. The average score of students in cycle II in writing poetry using the Quantum Writer method after receiving action was 85.05 or in the good category. The results show that the value obtained includes the high criteria. The results show that the value obtained includes the high criteria. Based on the results, it is known that the application of the Quantum Writing learning method in class X TP2 of SMK KB Pusdikpal can improve learning to write poetry.